Historicity of nursing graduate studies in Brazil: an analysis of the Sociology of the Professions - Fernanda Alves dos Santos Carregal; Biannka Melo dos Santos; Helena Pereira de Souza; Fernanda Batista Oliveira Santos; Maria Angélica de Almeida Peres; Maria Itayra Coelho de Souza Padilha (Associação Brasileira de Enfermagem, 2021)
ABSTRACT Objectives: to analyze the scientific productions about the history of graduate studies in Brazilian nursing in the light of Eliot Freidson's Sociology of the Professions. Methods: an integrative review, carried out in the databases indexed in Virtual Health Library. The Preferred Reporting Items for Systematic Reviews and Meta-Analyses recommendations were followed. Thematic content analysis and Eliot Freidson's concepts were adopted. Results: two categories emerged: "Institutionalization of graduate courses in Brazilian nursing", highlighting the historical process of professionalization in nursing through transition from empirical to professional care, subsidized by the monopoly of the construction of one's own knowledge; "The scientific production of graduate nursing in Brazil", showing the strengthening of a new generation of nurse researchers, given the greater scientificity in teaching due to implementation of graduate studies. Final Considerations: the analyzes present the historicity of graduate studies' institutionalization, supporting the understanding of professionalization outlines of Brazilian nursing.